A preparation method of accelerator for water glass adhesive

By preparing a promoter for water glass adhesive, combined with materials such as phosphate, mixed inorganic salt and boron-enhanced aqueous resin, the problems of slow curing speed, poor humidity resistance and insufficient thermal stability and collapse performance at room temperature are solved, and higher curing speed, humidity resistance and high temperature stability are achieved.

CN119216520BActive Publication Date: 2025-04-01SHENYANG AIKESIBON IND MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411352376.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-04-01
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Traditional water glass adhesives have slow curing speed at room temperature, poor humidity resistance, and insufficient thermal stability and collapse performance in high-temperature environments, making it difficult to meet the production needs of complex casting processes and high-performance castings.

Method used

A method for preparing a promoter for water glass binder is adopted. By mixing a phosphate solution with a reinforcement composed of mixed inorganic salt and boron-enhanced aqueous resin, modified starch, etc., a stable structure is formed, and the high temperature stability and crumbability of the sand type are improved.

Benefits of technology

It significantly improves the curing speed, moisture resistance and high temperature stability of water glass adhesive, enhances the fluidity and collapse of the sand, and meets the production needs of complex casting processes and high-performance castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216520B_ABST
    Figure CN119216520B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an accelerator for a water glass binder, belongs to the technical field of bonding accelerators, and is used to solve the technical problems in the prior art that the water glass binder has a slow curing speed at room temperature, poor moisture resistance, and the high temperature resistance and collapse performance of a sand mold need to be further improved. The invention comprises the following steps: adding a phosphoric acid solution into a three-necked flask and stirring, raising the temperature of the three-necked flask to 85-95 DEG C, adding aluminum hydroxide into the three-necked flask in batches, stirring until the system is dissolved, and obtaining a phosphate solution. The invention combines a metal salt mixture solution by preparing a boron-reinforced water-based resin, a modified starch and a polyol polymer, and prepares an accelerator to enhance the water glass, thereby effectively improving the flow index of the molding sand and improving the instant strength, moisture resistance, high temperature resistance and collapse performance of the sand mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bonding accelerators, and in particular to a method for preparing a bonding accelerator for a water glass bonding agent. Background Art

[0002] In the foundry industry, the performance of the binder is one of the key factors to ensure the strength, precision and final casting quality of the sand mold. Water glass (sodium silicate), as an inorganic binder with a long history, occupies an important position in the preparation of casting sand molds due to its good adhesion, low cost and environmental protection characteristics. However, with the continuous advancement of modern casting technology and the increasing requirements for casting quality, the performance of traditional water glass binders is difficult to meet the production needs of complex casting processes and high-performance castings.

[0003] Prior art, a Chinese invention patent with publication number CN104338893A, discloses a water glass sand with high fluidity and a preparation method thereof, wherein the modulus of the water glass used is 2.2-2.8, and 1%-10% (wt%) of alkali metal inorganic matter and 5%-15% (wt%) of amorphous phosphate are added to the water glass when preparing the water glass, and the fluidity of the water glass sand is improved by modifying the water glass and adding a fluidity promoter during sand mixing, thereby solving the problem of poor fluidity of the water glass sand, which is of great significance to the application of water glass sand and the development of green casting.

[0004] Traditional water glass binders have a slow solidification speed at room temperature and poor moisture resistance, making it difficult to meet the needs of rapid production. The above-mentioned alkali metal inorganic substances and amorphous phosphates only enhance the fluidity of the molding sand when reinforcing water glass. However, for castings with high precision requirements, the sand mold to be formed needs to have good thermal stability in a high temperature environment to avoid high-temperature expansion causing changes in the internal volume of the sand mold, resulting in excessive dimensional deviation of the casting sample. In addition, water glass, alkali metal inorganic substances and amorphous phosphates will form a complex cross-linked network in the sand mold after high-temperature treatment, resulting in the sand mold becoming hardened into blocks after being poured with molten high-temperature metal melt, with poor disintegration, making it difficult to separate it from the cast object and recycle it, which is not in line with the green and environmentally friendly manufacturing concept.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an accelerator for a water glass binder, which is used to solve the technical problems in the prior art that the water glass binder has a slow curing speed at room temperature, poor moisture resistance, and the high temperature resistance and collapse performance of the sand mold need to be further improved.

[0007] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing an accelerator for a water glass adhesive comprises the following steps:

[0008] S1. Add the phosphoric acid solution into a three-necked flask and stir. Raise the temperature of the three-necked flask to 85-95° C., add aluminum hydroxide into the three-necked flask in batches, and stir until the system is dissolved to obtain a phosphate solution.

[0009] S2. Add the mixed inorganic salts to the three-necked flask containing the phosphate solution in batches, continue to keep warm and stir until the system is dissolved, and naturally cool to room temperature to obtain a mixed solution;

[0010] S3. Add the enhancer to the three-necked flask containing the mixed solution, and stir at room temperature until the system is dissolved to obtain the promoter.

[0011] Furthermore, in step S1, the mass fraction of the phosphoric acid solution is 55-65%, and the molar ratio of the phosphoric acid to aluminum hydroxide is 3:2.

[0012] Furthermore, in step S2, the usage ratio of the phosphate solution and the mixed inorganic salt is 15 mL:2-3 g, and the mixed inorganic salt is composed of zinc phosphate, magnesium sulfate and sorbitol in a weight ratio of 3:1:2.

[0013] Furthermore, in step S3, the enhancer is composed of boron-enhanced water-based resin, modified starch, polyethylene glycol 200, and polyvinyl alcohol in a weight ratio of 4:3:2:1, and the dosage ratio of the mixed solution to the enhancer is 8 mL:1 g.

[0014] Furthermore, the preparation method of the boron-enhanced water-based resin is as follows: triphenylborate, formaldehyde, sodium hydroxide and phenol are added to a three-necked flask and stirred, the temperature of the three-necked flask is increased to 85-95° C., the temperature is kept for reaction for 2-3 hours, 2-cresol is added to the three-necked flask, the temperature is kept for reaction for 90-120 minutes, and the boron-enhanced water-based resin is obtained by post-treatment.

[0015] The synthetic reaction formula of boron enhanced waterborne resin is:

[0016]

[0017] Where: R = -H / -CH2OH

[0018] The synthetic reaction mechanism of boron-enhanced waterborne resin is:

[0019] Triphenylborate is an organic boron compound. With sodium hydroxide as a catalyst, triphenylborate, phenol and 2-cresol react with formaldehyde to form hydroxymethylated phenolic compounds. These hydroxymethylated phenolic compounds are further polycondensed through a dehydration polycondensation reaction to form a high molecular weight phenolic resin.

[0020] Furthermore, the amount ratio of the triphenylborate, formaldehyde, sodium hydroxide, phenol and 2-cresol is 10g:30mL:0.3-0.5g:8.5g:3.5g, the formaldehyde is a 35-37wt% formaldehyde aqueous solution, and the post-treatment includes: after the reaction is completed, the temperature of the three-necked flask is reduced to 70-80°C, and the low-boiling point solvent is evaporated under reduced pressure to obtain a boron-enhanced water-based resin.

[0021] Further, the modified starch is processed by the following steps:

[0022] A1. Grind corn starch through a 100-mesh sieve and dry it in an oven at 100-110° C. for 6-8 hours to obtain pretreated starch;

[0023] A2. Add the pretreated starch and deionized water into a three-necked flask and stir. The temperature of the three-necked flask is increased to 65-75° C., add sodium hydroxide solution into the three-necked flask, keep warm and stir for 60-80 min, add the modifier into the three-necked flask, increase the temperature of the three-necked flask to 85-95° C., stir for 12-14 h, and obtain modified starch by post-treatment.

[0024] The synthetic reaction mechanism of modified starch is:

[0025] The corn starch is pretreated and then mixed with sodium hydroxide. The strong alkalinity of sodium hydroxide is used to destroy the hydrogen bonds of the starch granules or the partial structure of the crystalline region, increase the activity of the hydroxyl groups on the starch molecules, swell the starch granules and partially dissolve them. The epoxy groups on the modifier react with the hydroxyl groups on the starch molecules to form ether bonds for covalent connection, thereby giving the modified starch better water solubility and reactivity. The unreacted modifier, small molecular by-products and residual salts and other impurities are removed by dialyzing in a dialysis bag to obtain water-soluble modified starch.

[0026] Furthermore, in step A2, the amount ratio of the pretreated starch, deionized water, sodium hydroxide solution and modifier is 10g:60mL:5mL:3g, and the post-treatment includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, hydrochloric acid is added dropwise to the three-necked flask, the pH of the system is adjusted to 7, suction filtration is performed, the filtrate is loaded into a dialysis bag, and deionized water is used to dialyze until the liquid conductivity value in the dialysis bag is close to that of deionized water, and the mixture in the dialysis bag is transferred to a rotary evaporator with a water bath temperature of 60-70°C, and after most of the solvent is evaporated under reduced pressure, the solid is placed in a freeze dryer, and freeze-dried to constant weight to obtain modified starch, wherein the molecular weight cutoff of the dialysis bag is 8000-14000Da.

[0027] Furthermore, the preparation method of the modifier is: add epichlorohydrin and purified water into a three-necked flask and stir, reduce the temperature of the three-necked flask to 10-15°C, add diethylamine dropwise into the three-necked flask, keep warm and stir for 20-22h, add sodium hydroxide solution dropwise into the three-necked flask, keep warm and stir for 60-80min, and obtain the modifier by post-treatment.

[0028] The synthetic reaction formula of the modifier is:

[0029]

[0030] The synthetic reaction mechanism of the modifier is:

[0031] Diethylamine is a primary amine, and the hydrogen atom on its nitrogen atom has certain activity. In a low temperature environment, the primary amine on diethylamine acts as a nucleophilic reagent to attack the epoxy group on the epichlorohydrin molecule, and a ring-opening addition reaction occurs to generate an intermediate. In an alkaline environment, the hydroxyl group on the molecule of the intermediate closes the ring with the halogen to form an oxirane bond, and a modifier is prepared.

[0032] The mass spectrometry analysis data of the modifier are: m / z: 129.1154 (100.0%), 130.1187 (7.6%); elemental analysis: C, 65.07; H, 11.70; N, 10.84; O, 12.38.

[0033] Furthermore, the dosage ratio of epichlorohydrin and diethylamine is 1.1 mol:1 mol, the dosage ratio of epichlorohydrin and purified water is 5 g:3 g, and the post-treatment includes: after the reaction is completed, adding purified water and petroleum ether to a three-necked flask, stirring for 20-30 minutes, back-extracting the aqueous phase with petroleum ether twice, combining the organic phases and drying them, transferring the organic phase to a rotary evaporator with a water bath temperature of 50-60°C, and removing the solvent under reduced pressure to obtain a modifier.

[0034] The present invention has the following beneficial effects:

[0035] 1. The accelerator for water glass binder of the present invention is prepared by mixing boron-reinforced water-based resin, modified starch, polyethylene glycol 200 and polyvinyl alcohol to strengthen the mixed solution composed of phosphate and inorganic salt. Phosphate, zinc phosphate, magnesium sulfate and other inorganic salts play a filling and reinforcing role in the sand mold and cooperate with the boron in the boron-reinforced water-based resin to form a stable structure, thereby improving the dimensional stability of the sand mold in a high temperature environment. The modified starch cooperates with polyethylene glycol 200 and polyvinyl alcohol to construct a flow lubrication system in the sand mold to improve the fluidity of the molding sand during the pouring process. The boron-reinforced water-based resin, modified starch, polyethylene glycol 200, polyvinyl alcohol and water glass cooperate with each other to improve the moisture resistance of the sand mold. The boron-reinforced modified resin and modified starch decompose in a high temperature environment to form pores and channels in the sand mold, thereby promoting the collapse of the sand mold and improving the collapse of the sand mold.

[0036] 2. The accelerator for water glass binder of the present invention is a mixed solution composed of aluminum phosphate, zinc phosphate and magnesium sulfate. The boron atom in the boron-enhanced water-based resin molecule has an empty orbital. On the one hand, it can accept the lone pair of electrons from the oxygen atom in phosphates such as phosphate ions, aluminum phosphate, zinc phosphate or magnesium phosphate to form a coordination bond. On the other hand, it can combine with the silicon-oxygen bond in sodium silicate to form a more stable chemical bond, thereby enhancing the interaction between the resin and the sodium silicate and constructing a complex chemical cross-linking, thereby improving the cross-linking degree of the sand mold, inhibiting the expansion and deformation caused by thermal stress inside the sand mold, and improving the high-temperature expansion resistance of the material. The phenolic hydroxyl groups on the boron-enhanced water-based resin molecules can bind to the water The sodium silicate in the glass interacts with each other to form hydrogen bonds or ion exchange, thereby enhancing the bonding strength of the binder. The phenolic hydroxyl groups on the boron-enhanced water-based resin and the hydroxyl groups on the polyethylene glycol 200 and polyvinyl alcohol molecules can interact with the sodium silicate molecules in the water glass, thereby reducing the surface tension and viscosity of the water glass binder, improving its permeability and distribution uniformity in the molding sand, thereby improving the fluidity of the molding sand. Compounds containing hydroxyl groups can form hydrogen bonds with the silicon hydroxyl groups in the water glass, thereby enhancing the interaction between the water glass molecules and refining the polysilicate particles in the water glass, thereby expanding the cross-sectional area of ​​the water glass bonding bridge, making the structure of the water glass binder more stable and reducing the erosion effect of water molecules on it.

[0037] 3. The accelerator for water glass binder of the present invention is prepared by modifying corn starch and introducing hydrophobic functional groups into starch molecules to improve the ability to resist the erosion of water molecules, thereby improving the water resistance of the water glass binder. The modified starch molecules contain some hydrophilic groups and hydrophobic groups, which can form a lubricating film on the surface of the molding sand particles, thereby effectively reducing the friction generated by the direct contact between the molding sand particles, making the relative movement between the molding sand particles smoother, thereby improving the fluidity of the molding sand, and the amino, hydroxyl and other functional groups in the modified starch can form hydrogen bonds with the silicon hydroxyl groups in the water glass, thereby enhancing the interaction between molecules and improving the instant strength of the material. The modified starch and the boron-enhanced water-based resin are carbonized and decomposed in a high temperature environment, the bonding bonds between the sand particles of the sand mold are broken, the residual strength of the sand mold after high temperature treatment is reduced, the collapsibility of the sand mold is improved, and the molding sand is easy to be regenerated and recovered. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 It is the infrared spectrum of the boron-enhanced water-based resin in the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] The present embodiment provides a method for preparing a accelerator for a water glass adhesive, comprising the following steps:

[0043] S1. Preparation of boron-enhanced waterborne resin

[0044] Weigh: 100 g of triphenylborate, 300 mL of 35 wt% formaldehyde aqueous solution, 3 g of sodium hydroxide and 85 g of phenol, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 85° C., keep warm for 2 h, add 35 g of 2-cresol into the three-necked flask, keep warm for 90 min, lower the temperature of the three-necked flask to 70° C., evaporate the low boiling point solvent under reduced pressure, and obtain a boron-enhanced water-based resin.

[0045] S2. Preparation of modified starch

[0046] Weigh: 101.8 g of epichlorohydrin and 61.1 g of purified water are added to a three-necked flask and stirred. The temperature of the three-necked flask is lowered to 10° C., 73.1 g of diethylamine is added dropwise to the three-necked flask, and the mixture is stirred for 20 h. 100 g of 35 wt% sodium hydroxide solution is added dropwise to the three-necked flask, and the mixture is stirred for 60 min. 100 mL of purified water and 300 mL of petroleum ether are added to the three-necked flask, and the mixture is stirred for 20 min. The aqueous phase is back-extracted with petroleum ether twice, and the organic phases are combined and dried. The organic phase is transferred to a rotary evaporator with a water bath temperature of 50° C., and the solvent is evaporated under reduced pressure to obtain a modifier.

[0047] The corn starch was crushed through a 100-mesh sieve and then placed in an oven at 100° C. and dried for 6 hours to obtain pretreated starch;

[0048] Weigh: 100g of pretreated starch and 600mL of deionized water are added to a three-necked flask and stirred. The temperature of the three-necked flask is increased to 65°C. 50mL of 35wt% sodium hydroxide solution is added to the three-necked flask, and the mixture is stirred for 60min. 30g of a modifier is added to the three-necked flask, and the temperature of the three-necked flask is increased to 85°C. The mixture is stirred for 12h. The temperature of the three-necked flask is lowered to room temperature. Hydrochloric acid is added dropwise to the three-necked flask to adjust the pH of the system to 7. The mixture is filtered and the filtrate is loaded into a dialysis bag with a molecular weight cutoff of 8000-14000Da. The mixture is dialyzed with deionized water until the liquid conductivity value in the dialysis bag is close to that of deionized water. The mixture in the dialysis bag is transferred to a rotary evaporator with a water bath temperature of 60°C. After most of the solvent is evaporated under reduced pressure, the solid is placed in a freeze dryer and freeze-dried to constant weight to obtain modified starch.

[0049] S3. Preparation of mixed solution

[0050] A 55 wt % phosphoric acid solution was added to a three-necked flask and stirred. The temperature of the three-necked flask was raised to 85° C. Aluminum hydroxide was added to the three-necked flask in batches and stirred until the system was dissolved to obtain a phosphate solution, wherein the molar ratio of phosphoric acid to aluminum hydroxide was 3:2;

[0051] Mix zinc phosphate, magnesium sulfate and sorbitol in a weight ratio of 3:1:2 to obtain a mixed inorganic salt;

[0052] Add mixed inorganic salts in batches to a three-necked flask containing phosphate solution, continue to keep warm and stir until the system is dissolved, and naturally cool to room temperature to obtain a mixed solution, wherein the dosage ratio of phosphate solution to mixed inorganic salts is 15mL:2g.

[0053] S4. Preparation of accelerator

[0054] The boron-reinforced water-based resin, modified starch, polyethylene glycol 200, and polyvinyl alcohol are uniformly mixed in a weight ratio of 4:3:2:1 to obtain a reinforcing agent;

[0055] The mixed solution and enhancer were added into a three-necked flask at a ratio of 8 mL:1 g, and stirred at room temperature until the system was dissolved to obtain the enhancer.

[0056] Example 2

[0057] The present embodiment provides a method for preparing a accelerator for a water glass adhesive, comprising the following steps:

[0058] S1. Preparation of boron-enhanced waterborne resin

[0059] Weigh: 100 g of triphenylborate, 300 mL of 36 wt% formaldehyde aqueous solution, 4 g of sodium hydroxide and 85 g of phenol, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 90° C., keep warm for 2.5 h, add 35 g of 2-cresol into the three-necked flask, keep warm for 105 min, lower the temperature of the three-necked flask to 75° C., evaporate the low boiling point solvent under reduced pressure, and obtain a boron-enhanced water-based resin.

[0060] S2. Preparation of modified starch

[0061] Weigh: 101.8 g of epichlorohydrin and 61.1 g of purified water are added to a three-necked flask and stirred. The temperature of the three-necked flask is lowered to 13° C., 73.1 g of diethylamine is added dropwise to the three-necked flask, and the mixture is stirred at this temperature for 21 h. 100 g of 40 wt % sodium hydroxide solution is added dropwise to the three-necked flask, and the mixture is stirred at this temperature for 70 min. 100 mL of purified water and 300 mL of petroleum ether are added to the three-necked flask, and the mixture is stirred for 25 min. The aqueous phase is back-extracted with petroleum ether twice. The organic phases are combined and dried. The organic phase is transferred to a rotary evaporator with a water bath temperature of 55° C., and the solvent is evaporated under reduced pressure to obtain a modifier.

[0062] The corn starch was crushed through a 100-mesh sieve and then placed in an oven at 105° C. to dry for 7 hours to obtain pretreated starch;

[0063] Weigh: 100g of pretreated starch and 600mL of deionized water are added to a three-necked flask and stirred. The temperature of the three-necked flask is increased to 70°C. 50mL of 40wt% sodium hydroxide solution is added to the three-necked flask, and the mixture is stirred for 70min. 30g of a modifier is added to the three-necked flask, and the temperature of the three-necked flask is increased to 90°C. The mixture is stirred for 13h. The temperature of the three-necked flask is lowered to room temperature. Hydrochloric acid is added dropwise to the three-necked flask to adjust the pH of the system to 7. The mixture is filtered and the filtrate is loaded into a dialysis bag with a molecular weight cutoff of 8000-14000Da. The mixture is dialyzed with deionized water until the liquid conductivity value in the dialysis bag is close to that of deionized water. The mixture in the dialysis bag is transferred to a rotary evaporator with a water bath temperature of 65°C. After most of the solvent is evaporated under reduced pressure, the solid is placed in a freeze dryer and freeze-dried to constant weight to obtain modified starch.

[0064] S3. Preparation of mixed solution

[0065] A 60 wt % phosphoric acid solution was added to a three-necked flask and stirred. The temperature of the three-necked flask was raised to 90° C. Aluminum hydroxide was added to the three-necked flask in batches and stirred until the system was dissolved to obtain a phosphate solution, wherein the molar ratio of phosphoric acid to aluminum hydroxide was 3:2;

[0066] Mix zinc phosphate, magnesium sulfate and sorbitol in a weight ratio of 3:1:2 to obtain a mixed inorganic salt;

[0067] Add mixed inorganic salts in batches to a three-necked flask containing phosphate solution, continue to keep warm and stir until the system is dissolved, and naturally cool to room temperature to obtain a mixed solution, wherein the dosage ratio of phosphate solution to mixed inorganic salts is 15mL:2.5g.

[0068] S4. Preparation of accelerator

[0069] The boron-reinforced water-based resin, modified starch, polyethylene glycol 200, and polyvinyl alcohol are uniformly mixed in a weight ratio of 4:3:2:1 to obtain a reinforcing agent;

[0070] The mixed solution and enhancer were added into a three-necked flask at a ratio of 8 mL:1 g, and stirred at room temperature until the system was dissolved to obtain the enhancer.

[0071] Example 3

[0072] The present embodiment provides a method for preparing a accelerator for a water glass adhesive, comprising the following steps:

[0073] S1. Preparation of boron-enhanced waterborne resin

[0074] Weigh: 100 g of triphenylborate, 300 mL of 37 wt% formaldehyde aqueous solution, 5 g of sodium hydroxide and 85 g of phenol, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 95° C., keep warm for 3 h, add 35 g of 2-cresol into the three-necked flask, keep warm for 120 min, lower the temperature of the three-necked flask to 80° C., evaporate the low boiling point solvent under reduced pressure, and obtain a boron-enhanced water-based resin.

[0075] S2. Preparation of modified starch

[0076] Weigh: 101.8 g of epichlorohydrin and 61.1 g of purified water are added to a three-necked flask and stirred. The temperature of the three-necked flask is lowered to 15° C., 73.1 g of diethylamine is added dropwise to the three-necked flask, and the mixture is stirred at this temperature for 22 h. 100 g of 45 wt% sodium hydroxide solution is added dropwise to the three-necked flask, and the mixture is stirred at this temperature for 80 min. 100 mL of purified water and 300 mL of petroleum ether are added to the three-necked flask, and the mixture is stirred for 30 min. The aqueous phase is back-extracted with petroleum ether twice, and the organic phases are combined and dried. The organic phase is transferred to a rotary evaporator with a water bath temperature of 60° C., and the solvent is evaporated under reduced pressure to obtain a modifier.

[0077] The corn starch was crushed through a 100-mesh sieve and then placed in an oven at a temperature of 110° C. and dried for 8 hours to obtain pretreated starch;

[0078] Weigh: 100g of pretreated starch and 600mL of deionized water are added to a three-necked flask and stirred. The temperature of the three-necked flask is increased to 75°C. 50mL of 45wt% sodium hydroxide solution is added to the three-necked flask, and the mixture is stirred for 80min. 30g of a modifier is added to the three-necked flask, and the temperature of the three-necked flask is increased to 95°C. The mixture is stirred for 14h. The temperature of the three-necked flask is lowered to room temperature. Hydrochloric acid is added dropwise to the three-necked flask to adjust the pH of the system to 7. The mixture is filtered and the filtrate is loaded into a dialysis bag with a molecular weight cutoff of 8000-14000Da. The mixture is dialyzed with deionized water until the liquid conductivity value in the dialysis bag is close to that of deionized water. The mixture in the dialysis bag is transferred to a rotary evaporator with a water bath temperature of 70°C. After most of the solvent is evaporated under reduced pressure, the solid is placed in a freeze dryer and freeze-dried to constant weight to obtain modified starch.

[0079] S3. Preparation of mixed solution

[0080] A 65 wt % phosphoric acid solution was added to a three-necked flask and stirred. The temperature of the three-necked flask was raised to 95° C. Aluminum hydroxide was added to the three-necked flask in batches and stirred until the system was dissolved to obtain a phosphate solution, wherein the molar ratio of phosphoric acid to aluminum hydroxide was 3:2;

[0081] Mix zinc phosphate, magnesium sulfate and sorbitol in a weight ratio of 3:1:2 to obtain a mixed inorganic salt;

[0082] Add mixed inorganic salts in batches to a three-necked flask containing phosphate solution, continue to keep warm and stir until the system is dissolved, and naturally cool to room temperature to obtain a mixed solution, wherein the amount ratio of phosphate solution to mixed inorganic salts is 15mL:3g.

[0083] S4. Preparation of accelerator

[0084] The boron-reinforced water-based resin, modified starch, polyethylene glycol 200, and polyvinyl alcohol are uniformly mixed in a weight ratio of 4:3:2:1 to obtain a reinforcing agent;

[0085] The mixed solution and enhancer were added into a three-necked flask at a ratio of 8 mL:1 g, and stirred at room temperature until the system was dissolved to obtain the enhancer.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 3 is that step S1 is eliminated and no boron-reinforced water-based resin is added in step S4.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 3 is that no modifier is added during the preparation of modified starch in step S2.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 3 is that step S2 is eliminated and modified starch is not added in step S4.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 3 is that polyethylene glycol 200 and polyvinyl alcohol are not added in step S4.

[0094] Performance Test:

[0095] The modulus is 2.8 and the density is 1.36 g / cm 3 The water glass solution and the accelerators prepared in Examples 1-3 and Comparative Examples 1-4 were added to a glass beaker at a volume ratio of 100:7 and stirred evenly to obtain a water glass binder. The water glass binder and the molding sand were mixed evenly at a dosage ratio of 93 g:7 mL;

[0096] The fluidity index of the sample was determined according to the standard GB / T 31057.3-2018 "Physical properties test of granular materials Part 3: Measurement of fluidity index";

[0097] Refer to the standard GB / T 2684-2009 "Test methods for foundry sand and mixtures" for the instant strength, residual strength and wet strength of the sample, where the instant strength is the strength of the sample after molding, the residual strength is the strength of the sample after high temperature treatment at 1000℃, and the wet strength is the strength of the sand mold after being placed in an environment with a humidity of 98% for 24 hours after curing;

[0098] The high temperature expansion rate of the sample was tested with reference to the standard GB / T 43365-2023 "Sand Mold Performance Test Method for Additive Manufacturing Metal Castings". The specific test results are shown in Table 1 below:

[0099] Table 1-Performance test data of samples

[0100]

[0101] Data Analysis:

[0102] Comparative analysis of the data in Table 1 above shows that the flow index of the accelerator prepared by the present invention to the water glass binder reaches 87, the instant strength of the sand mold prepared by the water glass binder reaches 2.88MPa, the wet strength reaches 2.80MPa, the residual strength reaches 0.63MPa, and the high temperature expansion rate is reduced to 0.31%. All performance parameters are higher than those of the comparative example;

[0103] It is explained that the present invention prepares a promoter to strengthen water glass by combining a metal salt mixture solution with a boron-reinforced water-based resin, modified starch and a polyol polymer, which not only effectively improves the flow index of the molding sand, but also improves the instant strength, moisture resistance, high temperature resistance and collapsibility of the sand mold.

[0104] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0105] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0106] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a accelerator for a water glass adhesive, characterized in that: The following steps are involved: S1. Add the phosphoric acid solution into a three-necked flask and stir. Raise the temperature of the three-necked flask to 85-95° C., add aluminum hydroxide into the three-necked flask in batches, and stir until the system is dissolved to obtain a phosphate solution. S2. Add the mixed inorganic salts to the three-necked flask containing the phosphate solution in batches, continue to keep warm and stir until the system is dissolved, and naturally cool to room temperature to obtain a mixed solution; S3, adding a reinforcing agent to the three-necked flask containing the mixed solution, stirring at room temperature until the system is dissolved, to obtain a promoter, wherein the reinforcing agent is composed of boron-reinforced water-based resin, modified starch, polyethylene glycol 200, and polyvinyl alcohol in a weight ratio of 4:3:2:1, and the amount ratio of the mixed solution to the reinforcing agent is 8mL:1g; Modified starch is processed by the following steps: A1. Grind corn starch through a 100-mesh sieve and dry it in an oven at 100-110° C. for 6-8 hours to obtain pretreated starch; A2, adding the pretreated starch and deionized water into a three-necked flask and stirring, raising the temperature of the three-necked flask to 65-75° C., adding sodium hydroxide solution into the three-necked flask, keeping warm and stirring for 60-80 min, adding the modifier into the three-necked flask, raising the temperature of the three-necked flask to 85-95° C., stirring for 12-14 h, and post-treating to obtain modified starch; The preparation method of the modifier is as follows: epichlorohydrin and purified water are added into a three-necked flask and stirred, the temperature of the three-necked flask is lowered to 10-15° C., diethylamine is added dropwise into the three-necked flask, the mixture is stirred for 20-22 hours, sodium hydroxide solution is added dropwise into the three-necked flask, the mixture is stirred for 60-80 minutes, and the modifier is obtained by post-processing.

2. The method for preparing a accelerator for a water glass adhesive according to claim 1, wherein: In step S1, the mass fraction of the phosphoric acid solution is 55-65%, and the molar ratio of the phosphoric acid to aluminum hydroxide is 3:

2.

3. The preparation method of a water glass adhesive accelerator according to claim 1, wherein In step S2, the usage ratio of the phosphate solution and the mixed inorganic salt is 15mL:2-3g, and the mixed inorganic salt is composed of zinc phosphate, magnesium sulfate and sorbitol in a weight ratio of 3:1:

2.

4. The method for preparing a accelerator for a water glass adhesive according to claim 1, wherein: The preparation method of the boron-enhanced water-based resin comprises the following steps: adding triphenylborate, formaldehyde, sodium hydroxide and phenol into a three-necked flask and stirring, raising the temperature of the three-necked flask to 85-95° C., keeping the temperature for reaction for 2-3 hours, adding 2-cresol into the three-necked flask, keeping the temperature for reaction for 90-120 minutes, and post-treating to obtain the boron-enhanced water-based resin.

5. The method for preparing a accelerator for water glass adhesive according to claim 4, wherein: The amount ratio of triphenylborate, formaldehyde, sodium hydroxide, phenol and 2-cresol is 10g:30mL:0.3-0.5g:8.5g:3.5g, the formaldehyde is a 35-37wt% formaldehyde aqueous solution, and the post-treatment comprises: after the reaction is completed, the temperature of the three-necked flask is reduced to 70-80°C, and the low boiling point solvent is evaporated under reduced pressure to obtain a boron-enhanced water-based resin.

6. The method for preparing a accelerator for water glass adhesive according to claim 1, wherein: In step A2, the amount ratio of the pretreated starch, deionized water, sodium hydroxide solution and modifier is 10g:60mL:5mL:3g, and the post-treatment includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, hydrochloric acid is added dropwise to the three-necked flask, the pH of the system is adjusted to 7, suction filtration is performed, the filtrate is loaded into a dialysis bag, and deionized water is used to dialyze until the liquid conductivity value in the dialysis bag is close to that of deionized water, and the mixture in the dialysis bag is transferred to a rotary evaporator with a water bath temperature of 60-70°C, and after most of the solvent is evaporated under reduced pressure, the solid is placed in a freeze dryer, and freeze-dried to constant weight to obtain modified starch, wherein the molecular weight cutoff of the dialysis bag is 8000-14000Da.

7. The method for preparing a accelerator for water glass adhesive according to claim 1, wherein: The dosage ratio of epichlorohydrin and diethylamine is 1.1 mol:1 mol, and the dosage ratio of epichlorohydrin and purified water is 5 g:3 g. The post-treatment comprises: after the reaction is completed, adding purified water and petroleum ether into a three-necked flask, stirring for 20-30 minutes, back-extracting the aqueous phase with petroleum ether twice, combining the organic phases and drying them, transferring the organic phase to a rotary evaporator with a water bath temperature of 50-60° C., and removing the solvent under reduced pressure to obtain a modifier.

Citation Information

Patent Citations

  • Sodium silicate sand with high fluidity and preparation method thereof

    CN104338893A

  • Sodium silicate reinforcing agent for casting and preparation method

    CN104226890A

  • Sodium silicate modifier, modified sodium silicate sand mold as well as preparation process and application of modified sodium silicate sand mold

    CN114436558A